Fear of vaginal birth and its associated factors among pregnant women attending the antenatal outpatient department at a tertiarylevel maternity hospital, Kathmandu - Maharjan, Anita; Thapa, Basanti; Maharjan, Sapana (Journal of Karnali Academy of Health Sciences, 2026)
Introduction: Pregnancy and childbirth are natural, but anxiety about motherhood, a condition called “tokophobia”, is common. The rate of cesarean sections is rising, often due to fear of vaginal birth (FOVB), linked to maternal age, occupation, and gestational age. FOVB can lead to adverse outcomes like fetal loss, lower birth weight, and longer or more complicated labor, sometimes requiring epidurals. The study aimed to assess FOVB levels and related factors among pregnant women at the antenatal outpatient department.Methods: This cross-sectional study, approved by NAMS IRB (Ref. no. 476), used purposive sampling to select 165 pregnant women at a tertiary hospital’s antenatal OPD in Kathmandu. Data were gathered through face-to-face interviews with a semistructured questionnaire. After cleaning and coding, analysis in SPSS v16 involved descriptive (frequencies, percentages, means, SDs) and inferential (Chi-square, Fisher’s exact) statistics.Results:Among 165 pregnant women, 53.9% expressed very positive emotions about the pregnancy, and 99% favored vaginal delivery, 33.3% experienced mild, 36.4% moderate, and 30.3% severe fear of vaginal birth (FOVB). Notably, FOVB showed no statistically significant association with socio-demographic factors, obstetric history, or family support.Conclusion: The study found two-thirds of respondents had significant fear. Midwives and obstetricians can improve care and counseling to help pregnant women overcome fears of vaginal birth. Focused counseling may boost vaginal birth preferences and lower fear-driven cesarean requests. Future research should include women from all trimesters to compare fear levels and counseling impact throughout pregnancy.